Keajaiban pantun Minang : arti dan tafsir - Sati, Darwis S. N. Sutan, 1934- (Bogor : Ar-Rahmah, 2005)
Interpretation of Minangkabau poems
Includes bibliographical references (p. 297)
Keywords: Indonesian poetry (Malay) -- History and criticism